2017
DOI: 10.1101/186270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal development of hippocampal subregions from childhood to adulthood

Abstract: Detailed descriptions of the development of the hippocampus promise to shed light on the neural foundation of development of memory and other cognitive functions, as well as the emergence of major mental disorders. Hippocampus is a heterogeneous structure with a well characterized internal complexity, but development of its distinct subregions in humans has remained poorly described. We analyzed magnetic resonance imaging (MRI) data from a large longitudinal sample (270 participants, 678 scans) using an automa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 94 publications
2
18
0
Order By: Relevance
“…Age and Sex were included as covariates in further analyses, in light of earlier findings that have suggested an ongoing development of hippocampal structure in the age range examined 12,15,89,90 , and given known sex differences in HPA axis functioning e.g., 43 as well as hippocampal subregions 14,89,91,92 . All indicator variables were converted to z-scores.…”
Section: Parenting Stress Measure the Parenting Stress Inventorymentioning
confidence: 99%
See 1 more Smart Citation
“…Age and Sex were included as covariates in further analyses, in light of earlier findings that have suggested an ongoing development of hippocampal structure in the age range examined 12,15,89,90 , and given known sex differences in HPA axis functioning e.g., 43 as well as hippocampal subregions 14,89,91,92 . All indicator variables were converted to z-scores.…”
Section: Parenting Stress Measure the Parenting Stress Inventorymentioning
confidence: 99%
“…Renewed interest in the developmental plasticity of the hippocampus has been fueled by recent findings from high-resolution magnetic resonance imaging (MRI) research. Together, the evidence reveals a heterochronous pattern of protracted maturation across hippocampal subregions that continues well into adolescence [11][12][13][14][15] and contributes to memory development 16 . This may be contrasted with prior suggestions that human hippocampal maturation occurrs by approximately 6 years of age [17][18][19] .…”
mentioning
confidence: 91%
“…Sex differences in the morphology, activation, and connectivity of the hippocampus: findings from human studies Men typically are reported to have larger volumes of both the left and right hippocampus than women [30] but once total brain volume or intracranial volume is used as a correction factor, there is no longer a significant sex difference [31]. Recent studies show no sex differences in hippocampal volume across development [32]. One caveat in these studies is that a number of factors that influence hippocampal volume are not often documented including early adversity (reductions are often seen in men but not in women: [33]), phase of menstrual cycle [34], parity status [35], hormone therapy [36], menopausal status [37], genotype [38], and testosterone levels in men [39].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we continue with two studies that illustrate how to predict these individual differences or predict an outcome from these individual differences in brain development. Specifically, the first study examines individual differences in the rate of within-individual change over time by modeling random intercepts and slopes in a linear mixed-effects model on 3wave longitudinal data (40). In a linear mixed-effects model (also referred to as multilevel modeling, or random-effects modeling), the fixed effects capture the average starting point (or intercept) and average change (slope) for the whole sample.…”
Section: Modeling Heterogeneity In Brain Developmentmentioning
confidence: 99%
“…They found that while the cornu ammonis (CA1) decreased in size on average across childhood and adolescence, the interindividual differences in the slope of change were substantial enough that including a random linear slope improved the overall model of this hippocampal subregion's development. By simply examining if the inclusion of a random slope for each participant improved their overall developmental model, Tamnes et al (40) were able to empirically test the presence of interindividual variability in the developmental pattern of their brain measure of interest. This is one example of a strategy that can be readily adopted in future longitudinal investigations of brain development with at least 3 time points.…”
Section: Modeling Heterogeneity In Brain Developmentmentioning
confidence: 99%